Experimental Study, Design and Production of Purple Basil Drying System with Solar Power and Comparison with Alternative Methods - Koca, Tarkan; Polat, Merve Nur (Fırat University, 2020)
In this study, solar energy supported basil drying system was designed and manufactured while conducting purple basil plant drying experiments. The experiments were carried out in three groups. In the first group of experiments, basil having were placed in the drying chamber and when the temperatures reached 45ºC, 50ºC, 55ºC, the mass was measured at one hour intervals. In the second group of experiments, when the temperature reached 45ºC, 50ºC, 55ºC, 60ºC in the dryer, basil having were put into the dryer and dried. In the third group of experiments basil having a starting mass of different were placed in the drying cabinet and dried. Drying times were between 3 and 7 hours depending on the temperature increase. After the completion of drying process, water activity and color analysis of the dried products were performed. The final moisture content of dried basil is reduced to less than 15%. Water activity values have been found below the 0,6 value specified in the literature and it has been concluded that it can be accepted as safe in terms of microbial growth. Drying times were found as expected in experiments at different temperatures. Color analysis experiments were carried out and required values were reached. As a result of the analysis, it was found that the manufactured system successfully enables the drying of basil.

Bu çalışmada güneş enerjisi ile reyhan kurutma sistemi tasarlanmış ve imalatı gerçekleştirilerek mor reyhan bitkisi kurutma deneyleri yapılmıştır. Deneyler üç grup şeklinde gerçekleştirilmiştir. Birinci grup deneylerde reyhanlar kurutma kabinine konmuş ve sıcaklıklar 45ºC, 50ºC, 55ºC ‘ye ulaştığında sabit tutulmuş ve birer saat aralıklarla kütle ölçümleri gerçekleştirilmiştir. İkinci grup deneylerde kurutma makinesinde sıcaklık 45ºC, 50ºC, 55ºC, 60ºC ‘ye ulaştığında sabit tutularak reyhanlar kurutma makinesinin içerisine konmuş ve kuruma gerçekleştirilmiştir. Üçüncü grup deneylerde farklı başlangıç kütlesine sahip reyhanlar kurutma kabinine konularak kurumaları sağlanmıştır. Kuruma süreleri 3 ile 7 saat arasında olmuştur. Kurutma işlemlerinin tamamlanmasının ardından kurutulan ürünlerin su aktivitesi ve renk analizi deneyleri yapılmıştır. Kurutulmuş reyhanın nihai nem içeriği %15'in altına düşürülmüştür. Su aktivite değerleri literatürde belirtilen 0,6 değerinin altında bulunmuş ve mikrobiyal büyüme açısından güvenli kabul edilebileceği sonucuna varılmıştır. Farklı sıcaklıklarda yapılan deneylerde kuruma süreleri beklendiği gibi bulunmuştur. Renk analizi deneyleri yapılmıştır. Analizler sonucunda imalatı gerçekleştirilen bu sistemin başarılı bir şekilde reyhanın kurutulmasına olanak sağladığı görülmüştür.
Güneş Enerjisi ile Reyhan Kurutma Sisteminin Tasarlanması, İmalatı, Deneysel İncelenmesi ve Alternatif Yöntemlerle Karşılaştırılması
Keywords: Engineering; Mühendislik